2012
DOI: 10.3389/fnbeh.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid transport inhibitor AM404 differentially modulates recognition memory in rats depending on environmental aversiveness

Abstract: Cannabinoid compounds may influence both emotional and cognitive processes depending on the level of environmental aversiveness at the time of drug administration. However, the mechanisms responsible for these responses remain to be elucidated. The present experiments investigated the effects induced by the endocannabinoid transport inhibitor AM404 (0.5–5 mg/kg, i.p.) on both emotional and cognitive performances of rats tested in a Spatial Open Field task and subjected to different experimental settings, named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 124 publications
4
25
0
Order By: Relevance
“…6). Cannabinoid effects on memory are highly dependent on the level of emotional arousal induced by the stressfulness of the experimental condition used in the different studies (6,13,27). Our findings are consistent with prior evidence in indicating that inhibitory avoidance training induces the release of the endocannabinoid AEA in the amygdala, hippocampus, and mPFC only under highly aversive conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6). Cannabinoid effects on memory are highly dependent on the level of emotional arousal induced by the stressfulness of the experimental condition used in the different studies (6,13,27). Our findings are consistent with prior evidence in indicating that inhibitory avoidance training induces the release of the endocannabinoid AEA in the amygdala, hippocampus, and mPFC only under highly aversive conditions.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported that endocannabinoid effects on memory consolidation depend on the level of emotional arousal at the time of encoding (6,13,27). Such findings suggest that an interaction with stress hormones is important in determining the modulatory effects of cannabinoids on memory processes.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the injection of ACPA into the medial septum or the nucleus accumbens shell induced memory consolidation deficit in a passive avoidance task (Najar et al, 2015) or the elevated plus maze test-retest paradigm respectively (Khodayar et al, 2015). This discrepancy in the effect of cannabinoids on memory formation may be related to strain differences, contexts (Manduca et al, 2014), drug specificity, genetic and environmental factors (Campolongo et al, 2012). Clinical studies also showed that the administration of cannabinoids impaired early and later stages of memory (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to what has been found with anxiety, the degree of stressfulness or aversiveness seems to contribute to the ability of eCB signaling to influence memory processes. With respect to memory acquisition, Campolongo et al (2012) showed that systemic injection of the AEA transport inhibitor AM404 impaired the acquisition of the novel object recognition task only in rats tested under higher stressful condition (ie, not handled and tested under bright light in an empty arena), without altering memory performance of rats tested under lower stressful condition (ie, extensively handled and tested under dim red light in an arena with familiar bedding (Campolongo et al, 2012). However, local infusions into discrete brain regions have given different results.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 99%